Validation of the emergency surgery score’s predictive accuracy for postoperative outcomes and ICU admissions in MENA vs. non-MENA emergency surgery patients - Mohamed Said Ghali (16810713) (2025)
Background The Emergency Surgery Score (ESS) has demonstrated strong predictive value for morbidity, mortality, and long-term survival outcomes. However, its applicability and validity in the Middle East and North Africa (MENA) region remain understudied. This research seeks to validate ESS's ability to predict postoperative outcomes, including 30-day mortality, complications, and ICU admissions, among patients undergoing emergency laparotomies (EL). Methods This retrospective study analyzed 230 EL cases from 2017 to 2021. ESS scores were calculated for each patient, and its predictive accuracy was compared with the American Society of Anesthesiologists (ASA) classification using c-statistic methodology. We also compared postoperative outcomes between MENA and non-MENA cohorts to assess potential regional variations in ESS performance. Results Out of 230 patients, 118 were from MENA and 112 from non-MENA regions. Sepsis was the most common diagnosis (69.6%). ICU admission was recorded in 63.4% of cases, and the 30-day mortality rate was 13.91%. ESS scores did not differ significantly between MENA and non-MENA patients (median: 7.5 vs. 7; P = 0.45). ESS outperformed ASA in predicting postoperative outcomes: complications (c-statistic: 0.79 vs. 0.73), ICU admissions (0.81 vs. 0.76), and mortality (0.86 vs. 0.78). Optimal ESS cutoffs for complications, ICU need, and mortality were 6, 8, and 10, respectively. ESS performed similarly across both MENA and non-MENA populations in predicting mortality, complications, and ICU admissions. Conclusion The ESS is a superior tool compared to ASA for predicting postoperative outcomes in emergency surgical patients, and it is applicable to diverse populations, including those from the MENA region. ESS enhances preoperative risk stratification, informs counseling decisions, and supports quality benchmarking across different healthcare settings. Future studies should address potential biases, including selection and information bias, and further explore ESS's role in different cultural contexts. Other Information Published in: European Journal of Trauma and Emergency Surgery License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00068-025-02888-6